Characteristics of Nurse Lecturers Affecting Identity of Students Regarding Humanized Nursing Care in Southern Nursing Colleges - Phetriang, Suleeporn; Nawsuwan, Kittiporn; Singweratham, Noppcha; Ratchathawan, Ratthayanaphit (Princess of Naradhiwas University Journal, 2019)
This predictive research aimed to study characteristics of nurse lecturers that affect the identity of nursing students regarding the humanized approach in nursing care among nursing students as perceived by nurse lecturers themselves. Sample was 136 nursing lecturers into the southern nursing college network. Sample size was calculated by using G* Power. Stratified random sampling was used. Research instrument was a questionnaire including nurse lecturers’ characteristics, and identity of nursing students in terms of humanized nursing care. The content validity was confirmed by three experts, yielding values ranged between .67-1.0. Reliability was examined using Cronbach’s alpha coefficient, yielding a value of .98. Data were analyzed using descriptive statistics, and multiple regression analysis with stepwise method.This predictive research aimed to study characteristics of nurse lecturers that affect the identity of nursing students regarding the humanized approach in nursing care among nursing students as perceived by nurse lecturers themselves. Sample was 136 nursing lecturers into the southern nursing college network. Sample size was calculated by using G* Power. Stratified random sampling was used. Research instrument was a questionnaire including nurse lecturers’ characteristics, and identity of nursing students in terms of humanized nursing care. The content validity was confirmed by three experts, yielding values ranged between .67-1.0. Reliability was examined using Cronbach’s alpha coefficient, yielding a value of .98. Data were analyzed using descriptive statistics, and multiple regression analysis with stepwise method. The results showed that perceived characteristics of the nurse lecturers in terms of technology management and administrative competency (Beta = .457, and .254, respectively) predicted 42.50% variance in the identity of nursing students in relation to humanized nursing care at a significance level of .001 (R2= .42.50). Therefore, the characteristics of nurse lecturers in relation to technology management and administrative competency should be promoted in order to concretely improve the identity of nursing students regarding humanized nursing care.